Outcomes of patients with acute respiratory failure on veno-venous extracorporeal membrane oxygenation requiring additional circulatory support by veno-venoarterial extracorporeal membrane oxygenation - Erlebach, Rolf; Wild, Lennart C.; Seeliger, Benjamin; Rath, Ann-Kathrin; Andermatt, Rea; Hofmaenner, Daniel A.; Schewe, Jens-Christian; Ganter, Christoph C.; Müller, Mattia; Putensen, Christian; Natanov, Ruslan; Kühn, Christian; et al. (Frontiers in Medicine, 2022)
Objective: Veno-venous (V-V) extracorporeal membrane oxygenation (ECMO) is increasingly used to support patients with severe acute respiratory distress syndrome (ARDS). In case of additional cardio-circulatory failure, some experienced centers upgrade the V-V ECMO with an additional arterial return cannula (termed V-VA ECMO). Here we analyzed short- and long-term outcome together with potential predictors of mortality. Design: Multicenter, retrospective analysis between January 2008 and September 2021. Setting: Three tertiary care ECMO centers in Germany (Hannover, Bonn) and Switzerland (Zurich). Patients: Seventy-three V-V ECMO patients with ARDS and additional acute cardio-circulatory deterioration required an upgrade to V-VA ECMO were included in this study. Measurements and main results: Fifty-three patients required an upgrade from V-V to V-VA and 20 patients were directly triple cannulated. Median (Interquartile Range) age was 49 (28-57) years and SOFA score was 14 (12-17) at V-VA ECMO upgrade. Vasoactive-inotropic score decreased from 53 (12-123) at V-VA ECMO upgrade to 9 (3-37) after 24 hours of V-VA ECMO support. Weaning from V-VA and V-V ECMO was successful in 47 (64%) and 40 (55%) patients, respectively. Duration of ECMO support was 12 (6-22) days and ICU length of stay was 32 (16-46) days. Overall ICU mortality was 48% and hospital mortality 51%. Two additional patients died after hospital discharge while the remaining patients survived up to two years (with six patients being lost to follow-up). The vast majority of patients was free from higher degree persistent organ dysfunction at follow-up. A SOFA score >14 and higher lactate concentrations at the day of V-VA upgrade were independent predictors of mortality in the multivariate regression analysis. Conclusions: In this analysis, the use of V-VA ECMO in patients with ARDS and concomitant cardiocirculatory failure was associated with a hospital survival of about 50%, and most of these patients survived up to 2 years. A SOFA score >14 and elevated lactate levels at the day of V-VA upgrade predict unfavorable outcome.